Microcomputer-assisted diagnosis of inherited disorders of the skeleton - Van Greunen, Francois (Division of Human Genetics, 2017)
Several hundred inherited disorders of the skeleton have been delineated. Individually these conditions are rare, but as a group they cause much crippling and hardship. Several factors, including the rarity and complexity of the manifestations of these conditions, as well as semantic overlap, impede the accurate diagnosis which is essential for effective treatment. In this regard, the adoption of microcomputers warrants evaluation as a high technology aid. Microcomputers have developed tremendous capabilities during recent years. The state of the art has become such that a diagnostic aid facility on such a device has been demonstrated in various disciplines of medicine and may also be feasible in the area of inherited skeletal disorders. The study which forms the basis of this thesis, concerns the investigation of this feasibility and has led to the development of an effective working model which sets the basis for microcomputer-aided diagnosis. The design features followed in this project are similar to those conventionally employed for "Expert systems" on mainframe computers. A comprehensive knowledge base consisting of over 200 skeletal disorders and 700 radiographic and clinical manifestations, has resulted. Furthermore, the application is capable of "learning", although inference as employed by the inference engines of real expert systems, is not employed. In this context learning implies that the knowledge base, with the passage of time, improves considerably when used by experts. Serendipitous findings in this regard are: • 1) Considerable improvement of existing profile descriptions can occur without any increased demands on computer memory and storage space; • 2) Growth of the knowledge base in the form of additional disease profiles can be effected with very modest inroads on memory and storage resources. The computerized diagnostic aid which resulted from this thesis, has been demonstrated to be successful in both the Department of Human Genetics of the University of Cape Town and the Department of Paediatrics of the Johannes Gutenberg University in Mainz. Evaluated both in terms of efficiency and utility, the system provides an enhancement to the specialist genetic diagnostician. These achievements have been effected by means of a unique newly developed application of compressed bit-mapping, attained by writing the applicable programs in Turbo Pascal and 8086- assembler languages. Calculations indicate that much larger data bases may possibly be implemented on present-day microcomputers by means of the methods developed in this project.